Solution of fractional bioheat equation in terms of Fox’s H-function - Damor, R. S. (Springerplus, 2016)
Present paper deals with the solution of time and space fractional Pennes bioheat equation. We consider time fractional derivative and space fractional derivative in the form of Caputo fractional derivative of order [Formula: see text] and Riesz–Feller fractional derivative of order [Formula: see text] respectively. We obtain solution in terms of Fox’s H-function with some special cases, by using Fourier–Laplace transforms.